Associations of single nucleotide polymorphisms in precursor-microRNA (miR)-125a and the expression of mature miR-125a with the development and prognosis of autoimmune thyroid diseases. (1st October 2014) - Inoue, Y; Watanabe, M; Inoue, N; Kagawa, T; Shibutani, S; Otsu, H; Saeki, M; Takuse, Y; Hidaka, Y; Iwatani, Y
Summary: It is important to search the biomarker to predict the development and prognosis of autoimmune thyroid diseases (AITDs) such as Hashimoto's disease (HD) and Graves' disease (GD). MicroRNA (miR) bind directly to the 3′ untranslated region of specific target mRNAs to suppress the expression of proteins, promote the degradation of target mRNAs and regulate immune response. miR-125a is known to be a negative regulator of regulated upon activation normal T cell expressed and secreted (RANTES), interleukin (IL)-6 and transforming growth factor (TGF)-β; however, its association with AITDs remains unknown. To clarify the association between AITDs and miR-125a, we genotyped the rs12976445 C/T, rs10404453 A/G and rs12975333 G/T polymorphisms in the MIR125A gene, which encodes miR-125a, using direct sequencing and polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) methods in 155 patients with GD, 151 patients with HD and 118 healthy volunteers. We also examined the expression of miR-125a in peripheral blood mononuclear cells (PBMCs) from 55 patients with GD, 79 patients with HD and 38 healthy volunteers using quantitative real-time PCR methods. We determined that the CC genotype and C allele of the rs12976445 C/T polymorphism were significantly more frequent in patients with HD compared with control subjects ( P < 0·05) and in intractable GD compared with GD in remission ( P < 0·05). The expression of miR-125a was correlated negatively with age ( P = 0·0010) and down-regulated in patients with GD compared with control subjects ( P = 0.0249). In conclusion, miR-125a expression in PBMCs and the rs12976445 C/T polymorphism were associated with AITD development and prognosis.